2003
DOI: 10.1046/j.1600-6135.2003.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus Allograft Nephropathy: Sequential Assessment of Histologic Viral Load, Tubulitis, and Graft Function Following Changes in Immunosuppression

Abstract: Our initial cases of polyoma virus allograft nephropathy (PVAN) received pulse steroids due to anxiety about concomitant acute rejection triggered by the presence of tubulitis. However, our current policy is to reduce immunosuppression in all cases. The aim of this study was to determine whether clinical followup in these patient categories shows any differences in: (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 12 publications
4
69
0
10
Order By: Relevance
“…18 Moreover, it has been shown that an early diagnosis before the onset of clinically apparent nephropathy is associated with improved outcomes in this entity, which portends a poor prognosis. 2,19 The current practice in the management of PVAN involves the judicious manipulation of immunosuppression, 9,10 once the diagnosis has been confirmed by tissue biopsy. 2,7 However, insufficient decrement of immunosuppression prevents adequate disease control, whereas over reduction is associated with an increased risk of allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Moreover, it has been shown that an early diagnosis before the onset of clinically apparent nephropathy is associated with improved outcomes in this entity, which portends a poor prognosis. 2,19 The current practice in the management of PVAN involves the judicious manipulation of immunosuppression, 9,10 once the diagnosis has been confirmed by tissue biopsy. 2,7 However, insufficient decrement of immunosuppression prevents adequate disease control, whereas over reduction is associated with an increased risk of allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 The cornerstone of PVAN management involves the reduction of immunosuppression in an attempt to restrain viral replication without inciting acute rejection. 9,10 Therefore, BKV DNA levels can guide the optimal level of immunosuppressive reduction and serve as a quantifiable surrogate marker of the course of infection. However, there appears to be limited data with regard to the presence and the level of BKV DNA in the plasma of renal transplant recipients without clinical evidence of PVAN.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, reduction in immunosuppression compared to pulse steroids was associated with reduction in cytopathic changes (83% vs. 20%; P=0.004) [53]. Pulse steroids did result in greater improvement in tubulitis (55% vs. 26%) but this effect was not associated with improvement in renal function.…”
Section: Management Of Biopsy Confirmed Bkvnmentioning
confidence: 88%
“…44,45 BKVN'de greft fonksiyon bozukluğu, kreatinin stabil seyretse bile tedaviye rağmen devam edebilir. 34,41,[46][47][48][49] Bunun yanında rejeksiyonun antilenfosit antikorlarla tedavisi de hastalığın ilerleyişini artırır. 49 Ayrıca, immünsupresyon tedavisinin değiştirilmesi ve azaltılması ile greft fonksiyonunda değişiklik olmadığını belirten yayınlar da vardır.…”
Section: Tarama Testleri̇unclassified